Understanding the social implications of digital agricultural technologies - Jenny Melo-Velasco; Kelly Wilson; Mary Hendrickson; Corinne Valdivia (Journal of Agriculture, Food Systems, and Community Development)
The current digital agricultural revolution presents significant possibilities, promising transformative changes in agri-food systems. While advocates foresee enhanced efficiency, profitability, and sustainability, social movements and social critical scholars have concerns about its potential to perpetuate existing inequalities in the food system. The current conversation on the social implications of digital technologies often lacks a balanced perspective, either too broad and generic in scope or too narrowly focused on specific technologies. This imbalanced approach makes it difficult to inform meaningful policy debates or guide stakeholders who want to harness digital technologies to create more equitable and inclusive food systems.